Distance effects, social class and the decision to participate in higher education in Ireland - John Cullinan; Darragh Flannery; Sharon Walsh; Selina McCoy (The Economic and Social Research Institute (ESRI), 2012)
While a number of international studies have attempted to assess the influence of geographic accessibility on the decision to participate in higher education, this issue has not been addressed in detail in an Irish context. The aim of this paper is to fill this gap and to present a higher education choice model that estimates the impact of travel distance on the decision of school leavers to proceed to higher education in Ireland, while also controlling for a range of individual level characteristics and school related variables. To do so we use data from the 2007 wave of the School Leavers' Survey. We find that, on average, travel distance is not an important factor in the higher education participation decision, when factors such as student ability are accounted for. However, further analysis shows that travel distance has a significantly negative impact on participation for those from lower social classes and that this impact grows stronger as distance increases. We also find that the distance effects are most pronounced for lower ability students from these social backgrounds. This has important implications for higher education policy in Ireland, especially in relation to equity of access and the design of the maintenance grant system.
Keywords: 330